Keterbatasan Ombudsman Menyelesaikan Perkara Korupsi Kolusi dan Nepotisme: Penelitian - Zulkifli; Ismail; Dhoni Martien (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
The Ombudsman of the Republic of Indonesia, as an institution that assists in managing public services, plays an important role in the effective and efficient administration of public services. However, it is acknowledged that there are still issues in the implementation of public service oversight. First, the Ombudsman of the Republic of Indonesia is still unable to transfer its authority to invited parties because many believe that the Ombudsman should not be invited. Second, there are constraints due to the absence of regulations regarding the approval and sanctions that the Ombudsman must enforce. Third, there is no enforcement of penalties by the Government for the cancellation of public services by local government heads, as recommended by the Indonesian Ombudsman. Both the government and the general public must support the implementation of public administration oversight by the Ombudsman to promote the well-being of society.